Exploitation versus Exploration in Multinational Firms: Implications for the Future of International Business - Leseure, M; Driouchi, T (Cranfield University, 2010)
Given the economic weight of multinational corporations and their privileged access to resources, many different scenarios can be built about the future of international business and about the future impact of international business on economic, technological, and social development. In this paper, we argue that multinationals do not form a uniform organisational population, and we provide empirical evidence of the existence of traditional, rigid entities seeking benefits from low-risk exploitative strategies on one hand, and of flexible multinationals seeking higher performance levels by balancing the trade-offs between exploration and exploitation on the other hand. As these two sub- populations compete with one another for resources, we use a population ecology perspective to study likely ecological scenarios for the future. Our conclusion is that traditional multinationals tend to prevail over flexible multinationals, and the conditions required for a future society to allow a genuine growth of flexible multinationals are unlikely. This implies that multinationals remain primarily exploitative, and that as such, they will only be associated with marginal economic, technological, and social developments in the future. Other organisational forms, such as entrepreneurial small business and communities of practices are shown to be much more likely vehicles through which society can progress and innovate.